Mimetic Posthumanism : Homo Mimeticus 2.0 in Art, Philosophy and Technics - Lawtoo, Nidesh, (Critical Posthumanisms ;, 2025)
It is tempting to affirm that on and about November 2022 (post)human character changed. The revolution in A.I. simulations certainly calls for an updated of the ancient realization that humans are imitative animals, or homo mimeticus . But the mimetic turn in posthuman studies is not limited to A.I.: from simulation to identification, affective contagion to viral mimesis, robotics to hypermimesis, the essays collected in this volume articulate the multiple facets of homo mimeticus 2.0. Challenging rationalist accounts of autonomous originality internal to the history of Homo sapiens , this volume argues from different-artistic, philosophical, technological-perspectives that the all too human tendency to imitate is, paradoxically, central to our ongoing process of becoming posthuman.